(untitled) (International Journal of Engineering and Computer Science, 2015)
In this paper we consider the weak signal leading to barely audible conversations and continuously dropped calls and loss of data connection in cell phones. This paper introduces a novel product called The Network extender which conquers this wireless dead zone. It strengthens weak cellular signals to deliver high quality signals for voice, data and video reception on cell phones. Here we are introducing adaptive echo cancelling digital processing which helps Performance of the Network extender. All idea is about bringing the base station nearer to Cell phone